Impact of the Fiber Length Distribution on Porous Sponges Originating from Short Electrospun Fibers Made from Polymer Yarn. Issue 2 (13th January 2020) - Liao, Xiaojian; Hu, Pin; Agarwal, Seema; Greiner, Andreas
Abstract: Ultralight highly porous sponges made of short electrospun polymer fibers have gained significant attention for a variety of applications. According to the established procedures, short electrospun fibers are obtained by cutting or homogenization of electrospun fibers in suspension, which yield fibers with inhomogeneous fiber length. The role of the fiber length distribution and the fiber length in the mechanical compressibility of the sponges is unknown. Therefore, as a model study, sponges made from suspensions of short electrospun poly(acrylonitrile) (PAN) fibers with controlled fiber length distribution are investigated, and the role of the fiber length distribution in the compressibility of the sponges is analyzed quantitatively. These sponges are also compared to the ones prepared by established procedure as a benchmark. It is found that the compression stress and modulus of ultralight sponges with monodisperse short fibers are respectively 32% and 45% higher than that made with polydisperse short fibers. The study also shows that sponges made from longer fibers have higher modulus in comparison to the sponges made from shorter fibers. Abstract : Ultralight highly porous sponges are obtained by freeze‐drying of suspensions of short fibers with well‐controlled length from electrospun yarn. The sponges with monodisperse short fibers show higher compression strength and modulus originating from short fiber dispersion with homogeneous fiber length.